Pengaruh Pemberian Pupuk Mono Kalium Phosphate MKP dan Ekoenzim Terhadap Pertumbuhan Serta Produksi dan Uji Metabolit Sekunder Tanaman Bawang Merah (Allium cepa L.) - Rahma, Yunita; Putra, Irwan Agusnu; Berliana, Yunida (UNIVERSITAS LABUHANBATU, 2025)
This study aims to determine the effect of MKP fertilizer and ecoenzyme, as well as to determine the effect of interaction on the application of MKP fertilizer and ecoenzyme in improving the quality of growth, production, and secondary metabolite content tests. This study was conducted from December 2024 to March 2025 in Klumpang Village, Hamparan Perak District, North Sumatra. Using a factorial randomized block design (RAK) with 2 treatment factors, each treatment repeated 3 times. The parameters observed were plant height (cm), number of leaves (strands), fresh plant weight (gr), wet tuber weight (gr), dry tuber weight (gr) and secondary metabolite tests on 6 compounds, namely alkaloids, flavonoids, terpenoids, saponins, and tannins. The results showed that MKP fertilizer had a significant effect on plant height at 4 WAP, 6 WAP, 8 WAP, plant weight parameters, wet tuber weight, and dry tuber weight. The best treatment was M1 (MKP dose of 10 gr/plant). Ecoenzyme treatment did not significantly affect all parameters. The interaction between MKP fertilizer and ecoenzyme did not significantly affect all parameters. The best treatment combination was M2E0 (MKP 20 grams/plant and ecoenzyme (control)). The phytochemical test of secondary metabolites in shallot (Allium cepa L) extracts continued to increase with increasing doses of MKP and ecoenzyme fertilizers. The best treatment was M2E2 (MKP 20 grams/plant and ecoenzyme 20 ml/liter of water) with results of 4 to 5 plus as shown in the lab results. Keywords: MKP, ecoenzyme, red onion, secondary metabolite